Determinación de especies forestales de interés hídrico en el Bosque Siempreverde Piemontano de la microcuenca Cañas - Dueñas Macías, Junior Michael (2022)
The objective of this research was to identify the forest species of water interest in the Piemont Evergreen Forest of the Cañas micro-basin of the Bolívar canton for the establishment of conservation strategies for natural channels. To carry out the investigation, the current state of the tree species of the study site was diagnosed, within which it was obtained that 25% of the sampled area corresponds to forest and 25% to agricultural use; thus, 33% of the sampled area within the micro-basin is deforested and 25% in forest transition. For the establishment of the species of hydric interest, information was collected through recognition cards, where average data of the diameter of height at the chest (1.56 m), height (16.95 m), basal area (0.65 m2) and volume (13.55 m3) to discover various characteristics of the forest species, yielding as results 10 species of medium level hydric interest, among which Samanea saman, Montingia calabura or Guazuma ulmifolia stand out, and 7 species with low level hydric interest. such as Ochroma pyramidale, Acnitus arborescens, Sesbania brenninohii. Subsequently, a conservation matrix for the micro-basin was carried out with strategies such as covering slopes with native vegetation, identification of riverbed intervention areas, and implementation of agroforestry systems with water recharge species in the areas where the riverbed flows. Evidencing that the determination of forest species of hydric interest allowed the formulation of strategies for the protection of natural channels of the Cañas micro-basin.